Low molecular weight heparin is useful in adult COVID-19 inpatients. Experience during the first Spanish wave: observational study - Jose Ramon Gonzalez-Porras; Moncef Belhassen-Garcia; Amparo Lopez-Bernus; Luis Mario Vaquero-Roncero; Beatriz Rodriguez; Cristina Carbonell; Raul Azibeiro; Alberto Hernandez-Sanchez; Jose Ignacio Martin-Gonzalez; Juan Miguel Manrique; Gloria Alonso-Claudio; Felipe Alvarez-Navia; et al. (São Paulo Medical Journal)
ABSTRACT BACKGROUND: The intensity of the thromboprophylaxis needed as a potential factor for preventing inpatient mortality due to coronavirus disease-19 (COVID-19) remains unclear. OBJECTIVE: To explore the association between anticoagulation intensity and COVID-19 survival. DESIGN AND SETTING: Retrospective observational study in a tertiary-level hospital in Spain. METHODS: Low-molecular-weight heparin (LMWH) status was ascertained based on prescription at admission. To control for immortal time bias, anticoagulant use was analyzed as a time-dependent variable. RESULTS: 690 patients were included (median age, 72 years). LMWH was administered to 615 patients, starting from hospital admission (89.1%). 410 (66.7%) received prophylactic-dose LMWH; 120 (19.5%), therapeutic-dose LMWH; and another 85 (13.8%) who presented respiratory failure, high D-dimer levels (> 3 mg/l) and non-worsening of inflammation markers received prophylaxis of intermediate-dose LMWH. The overall inpatient-mortality rate was 38.5%. The anticoagulant nonuser group presented higher mortality risk than each of the following groups: any LMWH users (HR 2.1; 95% CI: 1.40-3.15); the prophylactic-dose heparin group (HR 2.39; 95% CI, 1.57-3.64); and the users of heparin dose according to biomarkers (HR 6.52; 95% CI, 2.95-14.41). 3.4% of the patients experienced major hemorrhage. 2.8% of the patients developed an episode of thromboembolism. CONCLUSIONS: This observational study showed that LMWH administered at the time of admission was associated with lower mortality among unselected adult COVID-19 inpatients. The magnitude of the benefit may have been greatest for the intermediate-dose subgroup. Randomized controlled trials to assess the benefit of heparin within different therapeutic regimes for COVID-19 patients are required.